Approach to Neonates and Young Infants with Fever without a Source Who Are at Risk for Severe Bacterial Infection - Esposito, Susanna; Rinaldi, Victoria Elisa; Argentiero, Alberto; Farinelli, Edoardo; Cofini, Marta; D’Alonzo, Renato; Mencacci, Antonella; Principi, Nicola (Mediators of Inflammation, 2018)
Introduction. Among neonates and infants <3 months of age with fever without a source (FWS), 5% to 15% of cases are patients with fever caused by a serious bacterial infection (SBI). To favour the differentiation between low- and high-risk infants, several algorithms based on analytical and clinical parameters have been developed. The aim of this review is to describe the management of young infants with FWS and to discuss the impact of recent knowledge regarding FWS management on clinical practice. Materials and Methods. PubMed was used to search for all of the studies published over the last 35 years using the keywords: “fever without source” or “fever of unknown origin” or “meningitis” or “sepsis” or “urinary tract infection” and “neonate” or “newborn” or “infant <90 days of life” or “infant <3 months”. Results and Discussion. The selection of neonates and young infants who are <3 months old with FWS who are at risk for SBI remains a problem without a definitive solution. The old Rochester criteria remain effective for identifying young infants between 29 and 60 days old who do not have severe bacterial infections (SBIs). However, the addition of laboratory tests such as C-reactive protein (CRP) and procalcitonin (PCT) can significantly improve the identification of children with SBI. The approach in evaluating neonates is significantly more complicated, as their risk of SBIs, including bacteremia and meningitis, remains relevant and none of the suggested approaches can reduce the risk of dramatic mistakes. In both groups, the best antibiotic must be carefully selected considering the clinical findings, the laboratory data, the changing epidemiology, and increasing antibiotic resistance of the most common infectious bacteria.